Pengaruh Customer Experience dan Customer Value Terhadap Customer Loyalty Melalui Customer Satisfaction Sebagai Mediasi Pada Salama Meat Shop - Nafisah, Wardatun; Rizal, Mohammad; Athia, Ita (E-JRM : Elektronik Jurnal Riset Manajemen, 2025)
Abstract This study aims to analyze the influence of customer experience and customer value on customer loyalty through customer satisfaction as a mediation in Salama Meat Shop. The sampling technique used was to use the malhotra formula so that a sample of 80 respondents was obtained. The sampling technique used in this study by distributing questionnaires to Salama Meat Shop customers offline and online with a minimum of 2 purchases with the data analysis technique used is the Partial Least Square (PLS) approach. The data analysis methods used are measurement model or outer model test, validity test, reliability test, structural model test or inner model, using SmartPLS 3.0. The results of the study show that customer experience and customer value have a significant effect on customer loyalty. However, customer satisfaction does not have a significant effect on customer loyalty so that customer satisfaction cannot mediate customer experience and customer value to customer loyalty. Keywords: Customer Experience, Customer Value, Customer Loyalty, Customer Satisfaction.